The Model of Leadership Innovation Styles and Human Resource Development Utilized by World Class Universities - Ihkwanul, Ihkwanul; Aedi, Nur (CV. Publikasi Indonesia, 2025)
This research aims to find out the leadership style, innovation, and human resources used by the university. This type of research is qualitative research. Data collection was done by collecting 26 national and international articles related to the search keywords. Leadership, innovation, and human resource management are three key elements in the context of sustainable organizational development. This journal presents a systematic review of the literature related to these three aspects to gain an in-depth understanding of their relationship and impact on organizational performance. Through a comprehensive investigation of recent journal articles, the authors detail key findings in the literature spanning multiple disciplines.